The influence of gender on individuals' ability to predict their own risk tolerance: Evidence from a European country - Júlio Lob\~ao (Administrative Sciences, 2024)
Translation, adaptation, and validation of instruments for cross-cultural investigation requires a rigorous methodological procedure that should be carefully planned to deliver instruments with adequate reliability and validity. This process was applied to a questionnaire measuring Organizational Citizenship Behavior toward the Environment (OCBE), Organizational Identification (OI), Environmental Responsibility (ER), and Green Human Resources Management (GHRM) in Portuguese and Slovak organizations. Several methodological procedures for cross-cultural adaptation and validation of questionnaires were analyzed, most of which used independent translators, experts' analysis, and backward translation to the original language. In the present study, a procedure adapted from Beaton et al. (2000) was applied successfully, and the blind backward translations; expert committee; and the two pretests to assess content validity, functional equivalence, and clarity proved to be worthy. The psychometric properties were measured using a sample from Portugal (N = 122) and Slovakia (N = 269). Although employees were perceiving neither a strong environmental responsibility of their organizations nor strong green human resources management, they identified themselves with the organizations and engaged in OCBEs. Comparing both countries, the factorial structure was remarkably similar, highlighting the eco-helping actions and eco-civic engagement of OCBEs. Comparing both countries, the factorial structure was remarkably similar, highlighting the eco-helping actions and eco-civic engagement of OCBEs. The results indicated that the translated instrument was functionally equivalent to the original one, valid (scale CVI/Ave > 0.83), and reliable (Scale Alpha > 0.733) for evaluating the effect of employee practices and organization management in promoting and supporting environmental sustainability.The literature on individuals' ability to predict their own level of risk tolerance is scarce and presents divergent results. Utilizing both differential prediction models and logit models on a sample of 391 individuals in Portugal, this study demonstrates that respondents' gender play a crucial role in this predictive ability. Men tend to overestimate their level of risk tolerance, while women tend to believe they are less risk-tolerant than they actually are. Furthermore, the results reveal that men's ability to correctly predict their level of risk tolerance is significantly higher. Being a man implies a 20% higher probability of being consistent in this prediction compared to being a woman, even after controlling for a set of sociodemographic factors. The finding of a systematic inconsistency between measures of subjective and objective risk tolerance suggests that the choice between the two measures of risk propensity is not indifferent. Our findings have relevant implications in the fields of corporate finance, financial investment, and various other spheres of economic life.
Keywords: 350; gender; objective risk tolerance; Portugal; psychometric tests; risk tolerance; subjective risk tolerance; survey